Stan Toler's practical guide for ministry transition how to navigate pastoral change personally and professionally - Toler, Stan. (Indianapolis, Ind. : Wesleyan Pub. House, 2010)
Am I done here? Do I have something further to offer this congregation? Is it time to seek a leadership position elsewhere? Or is this merely a case of "spring fever"? Many pastors wrestle with questions like these each year, never sure if the time is right for a pastoral move. Veteran pastor Stan Toler comes alongside the pastor in transition to help assess the reasons for change and be sure that the decision to move--and the move itself--will go smoothly. Subjects include: assessing your leadership potential, assessing your leadership fit, reasons to consider a change, reasons to consider staying, selecting your next ministry setting, presenting yourself well in person and in print, interviewing, negotiating compensation, family moving do's and don'ts, establishing your new home, and the first 90 days of a new pastorate -- Vendor description.
Discernment : knowing when to move -- Perception : seeing greener grass for what it is -- Potential : discovering your leadership potential and ministry place -- Vision : understanding the need for change -- Perseverance : staying when you have an offer you can't refuse -- Succession : preparing for the one who follows you -- Preparation : getting ready for your next ministry assignment -- Mentoring : preparing your current congregation for transition -- Family : preparing those you love for transition -- Beginning : leading during the first ninety days.
Includes bibliographical references (p. [185]-192).
Description based on print version record.
Keywords: Clergy -- Relocation; RELIGION / Christian Ministry / Pastoral Resources; Electronic books